Utilization of Artificial Intelligence (AI) in Adapting Islamic Education Learning - Shavina, Fara; Fauzi, Amin (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to explore how artificial intelligence (AI) technology can be utilized in adapting Islamic Religious Education (PAI) learning. Using a descriptive qualitative research approach and my own fieldwork, this study was conducted through a literature review and the search for valid data generated from my fieldwork. This involved reviewing various data sources such as scientific journals, books, articles, and documents, as well as direct visits to schools to gather valid data for my research. Other digital resources discussed topics related to artificial intelligence (AI) and Islamic Religious Education (PAI) were also used. The results show that artificial intelligence (AI) has the ability to improve the effectiveness of the learning process and encourage active student engagement through an intelligent and adaptive recommendation system. Thus, the application of artificial intelligence (AI) in PAI learning has great potential to create a more relevant and efficient learning experience for students and can also provide fun and enjoyable learning motivation for students. Furthermore, students become more active and deliver improved learning outcomes compared to before.